Study of the effectiveness of the liberatory manoeuvre in Lindsay–Hemenway syndrome - A. Sánchez Gil-Hernández Urtiz; A. Herrera-Ortiz; M.A. Pérez-Cisneros (Revista Médica del Hospital General de México, 2016)
Introduction: Lindsay–Hemenway syndrome, also known as ischaemia of the anterior vestibular artery, was described in 1956 by J.R. Lindsay and W.G. Hemenway, although it was H.F. Schucknecht who discovered its vascular origin. It is a vertiginous syndrome associated with occlusion of the anterior vestibular artery. Ischaemic necrosis causes an acute long-lasting episode of rotatory vertigo. Subsequently, degeneration of the otolithic macula and the accumulation of disperse otoconia in the cupula of the posterior semicircular canal cause benign paroxysmal positional vertigo. Material and methods: A comparative, prospective, multicentre clinical study was conducted from October 2013 to July 2014 at the Ear, Nose and Throat Department of Hospital Regional Dr. Valentín Gómez Farías, Instituto de Seguridad y Servicios Sociales de los Trabajadores del Estado, and Hospital General de Zapopan. Patients with Lindsay–Hemenway syndrome were identified and initially treated with vestibular rehabilitation exercises. Patients who did not improve after one month were treated using Semont's liberatory manoeuvre. The clinical outcome of the manoeuvre was classified as total cure, partial cure or no improvement. Results: A total of 12 patients were included in the study. Following the first liberatory manoeuvre, 9 patients (75%) presented total cure, 2 patients (16%) presented partial cure and 1 patient (8%) no improvement. Following the second manoeuvre, 2 of the 3 patients with partial cure presented total cure (92%) and one patient still presented no improvement (8%). Discussion: We concluded that Semont's liberatory manoeuvre is highly effective in patients presenting Lindsay–Hemenway syndrome.